Work and tax evasion incentive effects of social insurance programs. Evidence from an employment-based benefit extension - Marcelo Bergolo; Guillermo Cruces (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2014)
This article studies how social insurance programs shape individual's incentives to take up registered employment and to report earnings to the tax authorities. The analysis is based on a social insurance reform in Uruguay that extended healthcare coverage to the dependent children of registered private-sector workers. The identification strategy relies on a comparison between individuals with and without dependent children before and after the reform. The reform increased benefit-eligible registered employment by 1.6 percentage points (about 5 percent above the prereform level), mainly due to an increase in labor force participation rather than to movement from unregistered to registered employment. The shift was greater for parents with younger children and for cohabiting adults whose partners' jobs did not provide the couples' children with access to the benefit. Finally, the reform increased the incidence of underreporting of salaried earnings by about 4 percentage points (25 percent higher than the pre-reform level), mostly for workers employed at small firms. The increase in fiscal revenue from higher levels of registered employment was several orders of magnitude greater than the loss of revenue due to an increase in underreporting.
Keywords: J22; H26; O17; 330; labor supply; work incentives; social insurance; tax evasion